A statistical approach to covering lemmas. (August 2015) - Sanders, Tom
Abstract: We discuss a statistical variant of Ruzsa's covering lemma and use it to show that if G is an Abelian group of bounded exponent and A ⊂ G has | A + A | ⩽ K | A | then the subgroup generated by A has size at most exp ( O ( K log 2 2 K ) ) | A |, where the constant in the big- O depends on the exponent of the group only.